Meningkatkan aktifitas dan hasil belajar peserta didik melalui model pembelajaran Teams Games Tournament (TGT) menggunakan media “ATM BCA” - Sutrisno Sutrisno (Universitas Negeri Malang, 2019)
Learning models or media that are appropriate to the characteristics of the material, and students can increase the effectiveness of learning. Models that can involve students can improve understanding of the material and the same conditions also apply to media that are by the characteristics of the material. Teams Games Tournament (TGT) learning model using the media